ANALISIS TETUA DAN LEGITIMASI HASIL PERSILANGAN TERKONTROL PADA TANAMAN KELAPA SAWIT MENGGUNAKAN MARKA SSR - Hani (Program Studi Agroteknologi INSTIPER, 2019)
The oil palm gives the highest yields per hectare of all oil crops at present. The high and increasing yields of the oil palm have led to a rapidly expanding world industry, now based in the tropical areas of Asia, Africa and America. The switch to the D x P or T hybrid planting material can increase productivity per unit area. However controlled pollination of oil palms is difficult and prone to various sources of error. Illegitimacy is a silent factor that has a negative impact on controlled crossing in the oil palm. Illegitimacy can happen in any stage of the controlled crosses in the oil palm, from the initial stage of selecting and labeling parents, to the initial stage in field trial. The use of molecular markers improves the integrity of breeding programs in perennial crops such as oil palm. In plant breeding programmes, it is important to know the parentage of families and individuals for a variety of reasons. SSR analysis can be used for correct parentage assignment in progeny trials of oil palm. Paternity analysis of 83 half sibs progenies from 5 female parents and one male parent with 16 SSR markers detected all individual that clearly belong to the family they were assigned. Keyword : Crosses, Legitimation, Parentage, Oil Palm, SSR